Pretreatment of dentine as a strategy to improve adhesion: a literature review - Choque Apaza, Wilson Zacarías (2022)
Dentin treatment as a prior step to the adhesion procedure is intended to improve the substrate condition by improving the bonding strength between the tooth surfaces and the restorative material, promoting greater longevity and stability of the restoration. The objective of the study was to carry out a review of the literature that describes the properties of different conditioning agents of dentin. A review of the literature was carried out, including works published between 2014 and 2020, from medical databases such as PubMeb, SciELO and ScienceDirect; in English, Spanish and Portuguese. A total of 20 articles that met the inclusion criteria were selected. The use of various dentin pre-treatment agents has been identified in the literature, mainly chemical agents such as sodium hypochlorite, chlorhexidine, ethylenediaminetetraacetic acid (EDTA), metallic nanoparticles and mechanical techniques such as air abrasion. with aluminum oxide and baking soda.